Energy Efficiency in Buildings: Numerical Study of the Impact of Integrating Phase Change Materials Into the Walls - Ouaouja, Zakaria; Ousegui, Abdellah (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
In order to improve the energy efficiency of lightweight envelopes, the solar energy storage using Phase Change Materials (PCMs) integrated into the walls is suggested as a passive solution, since PCMs are considered as one of the best materials for storing or releasing thermal heat as latent energy. For this specific reason a comparative study between structures with and without PCM has been developed to highlight the actual impact of the thickness, location and type of the PCM layer on the thermal behavior inside buildings and their impact on electricity consumption. An ASHRAE benchmark cases were chosen to validate the model. This numerical study was performed out using the "EnergyPlus V 9.0.1” building thermal simulation software, which accurately predicts the building’s temperature, humidity and energy consumption profiles as well as several other parameters.